Palm oil-based bioenergy sustainability and policy in Indonesia and Malaysia: A systematic review and future agendas - Petir Papilo; Marimin Marimin; Erliza Hambali; Machfud Machfud; Mohamad Yani; Muhammad Asrol; Evanila Evanila; Hermawan Prasetya; Jaizuluddin Mahmud (Heliyon, 2022)
This paper reviews previous research on the sustainability and policies of palm oil-based bioenergy in Indonesia and Malaysia. A systematic literature review with a meta-analysis (PRISMA) methodology was performed to evaluate the related articles discussing sustainability and bioenergy policies. This study found 96 articles that mapped the sustainability and policies of bioenergy in Indonesia and Malaysia over the last decade. The sustainability studies were divided into two areas: the environment and socioeconomics. Researchers were more likely to examine environmental factors than socioeconomic factors, specifically focusing on the following environmental indicators: land use conversion, deforestation, and CO2 emissions. Most policy studies concentrated on sustainability and energy security. Over the last two decades, the development of bioenergy policies in Indonesia and Malaysia has been comparable in terms of geographical position and palm oil production. However, Indonesia's bioenergy policy has tended to be more vigorous and dynamic than Malaysia.